Porcine umbilical cord matrix stem cells - R Carlin; Deryl L Troyer; Mark L Weiss; Bruce D Schultz; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 2006)
Since their discovery in 2000, pig umbilical cord stem cells have been studied at KState. The studies have been expanded to included other species, including humans. In addition, other research groups around the world have published scientific studies with these cells. Their unique attributes include being plentiful, easily collected, and (in humans) non-controversial. Initial work in the pig has concentrated on characterizing the cells to understand how they compare with other populations of stem cells. Results indicate that they have several characteristics in common with other primitive stem-cell populations, and that they are relatively easy to work with in the laboratory.; Swine Day, 2006, Kansas State University, Manhattan, KS, 2006
Keywords: Kansas Agricultural Experiment Station contribution; no. 08-83-S; Swine day; 2006; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 966; Pigs; Stem cell; Umbilical cord; Wharton' s jelly; Swine